PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP IMPLEMENTASI KNOWLEDGE MANAGEMENT DI PT. JASA RAHARJA (PERSERO) CABANG SUMATERA BARAT - Helfan Syafli; Bustari Muchtar (Program Studi Magister Manajemen, 2015)
This research aimed to reveal the effect of: (1) transformational leadership on organizational culture in PT. Jasa Raharja Branch West Sumatera. (2) transformational leadership to the implementation of knowledge management in PT. Jasa Raharja Branch West Sumatera. (3) organizational culture on knowledge management implementation in PT. Jasa Raharja Branch West Sumatera. The population of this research was all employees at PT.Jasa Raharja Branch West Sumatera about 56 people. Sampling is done by means of proportional stratified random sampling about 49 people. The technique of data analysis used the path (path analysis). The results showed: (1) Transformational leadership significantly influence on organizational culture at PT. Jasa Raharja Branch West Sumatera. (2) Transformational leadership significantly influence the implementation of knowledge management at PT. Jasa Raharja Branch West Sumatera. (3) organizational culture significantly influence the implementation of knowledge management at PT. Jasa Raharja Branch West Sumatera. Keywords: transformastional leadership, organization culture, knowledge magement.